1105 A Randomized Controlled Trial of a Psychological Intervention for Decreasing Bedtime Procrastination: The BED-PRO Study. (27th May 2020) - Suh†, S; Kim, G; Jeoung, S; An, H
Abstract: Introduction: Bedtime Procrastination (BP) is defined as the behavior of going to bed later than intended, without having external reasons for doing so. Previous studies have shown that BP has a negative effect on sleep and health, and there is a need to develop interventions to decrease BP. This study (BED-PRO) is an ongoing study evaluating a behavioral intervention to reduce BP. Methods: Fifteen participants who scored higher than 33 on the Bedtime Procrastination Scale were randomized to either the treatment (TRT, n=6) or control group (CTRL, n=9). Treatment consisted of four face-to-face individual sessions. All participants completed self-report questionnaires on Bedtime Procrastination Scale (BPS), Epworth Sleepiness Scale (ESS), Positive Affect and Negative Affect Schedule (K-PANAS-R) and completed the 7-day sleep diary. Data was analyzed using two-way mixed Measures Analysis of Variance (ANOVA). Results: Mean age of the participants was 21.78 (±1.8) years and 80% (n=12) were females. Group by time interactions from repeated measures analyses revealed significant post intervention improvements in the TRT group compared to the CTRL group on all bedtime procrastination duration and scores, sleep efficiency, refreshment after waking, daytime sleepiness and negative affect of K-PANAS-R. Specifically, bedtime procrastination duration in the TRT group measured by sleep diaries decreased significantly from 75.30 (±58.57) min to 14.83 (±7.83) min, while the CTRL group did not change from 57.60 (±32.01) to 54.36 (±40.82) min (p=0.019). In addition, the TRT group reported significant improvements in bedtime procrastination scores from 36.00 (±4.05) to 22.50 (±6.72). Conclusion: Based on results, the behavioral intervention used in this study looks promising in improving bedtime procrastination and sleep. Support: This work was supported by the Ministry of Education of the Republic of Korea and the National Research Foundation of Korea(NRF-2018S1A5A8026807)